ADAPTAÇÃO E VALIDAÇÃO SEMÂNTICA DO THINKING STYLES INVENTORY – REVISED II (TSI-R2) PARA AS LICENCIATURAS EM MÚSICA NO BRASIL (Orfeu, 2020)
In this research, we adapted and sought semantic validation of the Revised Thinking Styles Inventory 2 (STERNBERG; WAGNER; ZHANG, 2007) – TSI-R2 – in order to measure different stages and means that are used to solve problems, execute tasks or projects and make decisions, having as specific objectives: a) adapting the instrument to the area of Music; b) evaluating the instrument adapted by judges from the areas involved; c) investigating understanding by target Audience. Methodologically, they are the procedures that are in accordance with the standards of the International Test Commission (2010), namely: agreement by the judges of the areas of Linguistics, Music and Musical cognition, and the confidence with robust evidence of the understanding from the target audience. The results of semantic validation show that the TSI-R2 can be used with graduates in Licenciate Music Degreee, as it has its construct preserved despite the elimination of some items during the research.
Keywords: evidence of validity; musical evaluation; musical cognition; psychometry